Theatrical discussion as a game (Jacob Mamontov and Les Kurbas) - Полякова, Юліана Юріївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The article contains an analysis of the discussion between the director Les Kurbas and the playwright Yakov Mamontov about the tragicomedy and its role in the development of the Ukrainian theater of the 1920s. The reception of this discussion in the works of famous contemporary theater critics such as Anna Veselovskaya and Marina Grinishina, which, based on controversy, make a projection of controversy for the further development of the Ukrainian theater. The author examines the controversy between two artists through the prism of the concept of J. Gejzinga. The scientist believed that the culture of mankind arises and develops as a game, in which philosophical disputes also have a game component. The author of the article analyzes the game component of the game component of this controversy, connected both with the personalities of the artists, and with the form of presentation of the material and format of the publication. By giving a brief description of the life and creative activity of both artists, the author comes to the conclusion that they were formed by different cultural traditions, and as a result, the current development of the theatrical process was perceived differently. Although Mamontov’s article, which began the discussion, was of a volatile nature, in this debate Mamontov played the role of the erudite professor who taught his opponent. Instead, Kurbas, in all his public speeches, positioned himself as a revolutionary from art, therefore expressed sharply and uncompromisingly, accusing his opponents of counterrevolution and retrogradeism. Mamontov believed that tragicomedy is a genre that is most in line with the era of revolutionary change, because it reflects the struggle of two antagonistic worlds. For those who have suffered defeat, the events of the present are a tragedy; those who won conquered the bourgeois comedy. Kurbas, on the other hand, proclaims that tragicomedia reflects the philistines who are trying to become heroes, so this genre is small and does not meet the requirements of the present. The author argues that Kurbas and Mamontov played distinct roles of opponents in this debate, because the creative practice of both artists testifies to the similarity of their artistic principles.